Website interactivity may compensate for consumers' reduced control in E-Commerce. (July 2019) - Wu, Linwan
Abstract: Existing research has confirmed that consumers may experience reduced control over product consumption when facing new products or limited product choices. This research predicts that interactivity of a retailing website may compensate for consumers' reduced control in E-Commerce. To test this prediction, two studies were conducted to analyze the influence of interactivity on product evaluation in situations of reduced control. Study 1 discovered that participants primed with a strong desire for control expressed more favorable attitudes toward a new product when interactivity was high versus low. In Study 2, participants with a strong desire for control evaluated a small choice set more favorably when interactivity was high versus low. Both studies also identified the positive main effect of interactivity on product attitude. The theoretical and practical implications of these findings are discussed.